A New Horizon in Chitosan Research: Silkworm-Derived Biopolymer and Its Applications - , Bhuvaneshwar Rajesh Naik; , Amarnatha, N.; , Kruthika, M. S.; , Pritish Chavan; , Praveen Kumar Gowda N. M.; , Rakshitha, M. P. (Archives of Current Research International, 2025)
Chitosan, a biodegradable biopolymer traditionally sourced from crustaceans, has growing significance in the food, biomedical and environmental sectors. However, concerns over allergenicity, heavy metal contamination and seasonal availability necessitate alternative sources. Silkworm pupae, an underutilized by-product of India's silk industry, offer a sustainable and efficient alternative. Chitosan extracted from silkworm pupae exhibits superior physicochemical properties, including high solubility (>98%), low ash content (<1%) and a high degree of deacetylation (>85%), along with excellent antimicrobial, film-forming and biocompatible characteristics. Compared to shrimp shell-derived chitosan, it demonstrates a higher molecular weight and purity, with potential applications in food preservation, pharmaceuticals, textiles and sericulture. This review highlights the extraction techniques, structural attributes and multi-sectoral applications of pupal chitosan, advocating for its commercial development as a viable, eco-friendly substitute for conventional chitosan sources.